A Retrospective Analysis of Pedicle Screw Placement Accuracy Using the ExcelsiusGPS Robotic Guidance System: Case Series. Issue 3 (28th March 2023) - Kanaly, Charles W.; Backes, Danielle M.; Toossi, Nader; Bucklen, Brandon
Abstract : BACKGROUND: Robotic guidance has become widespread in spine surgery. Although the intent is improved screw placement, further system-specific data are required to substantiate this intention for pedicle screws in spinal stabilization constructs. OBJECTIVE: To determine the accuracy of pedicle screws placed with the aid of a robot in a cohort of patients immediately after the adoption of the robot-assisted surgery technique. METHODS: A retrospective, Institutional Review Board–approved study was performed on the first 100 patients at a single facility, who had undergone spinal surgeries with the use of robotic techniques. Pedicle screw accuracy was graded using the Gertzbein–Robbins Scale based on pedicle wall breach, with grade A representing 0 mm breach and successive grades increasing breach thresholds by 2 mm increments. Preoperative and postoperative computed tomography scans were also used to assess offsets between the objective plan and true screw placements. RESULTS: A total of 326 screws were analyzed among 72 patients with sufficient imaging data. Ages ranged from 21 to 84 years. The total accuracy rate based on the Gertzbein–Robbins Scale was 97.5%, and the rate for each grade is as follows: A, 82%; B, 15.5%; C, 1.5%; D, 1%; and E, 0. The average tip offset was 1.9 mm, the average tail offset was 2.0 mm, and the average angular offset was 2.6°. CONCLUSION: Robotic-assisted surgery allowed for accurate implantation of pedicle screws on immediate adoption of this technique. There were no complications attributable to the robotic technique, and no hardware revisions were required. Abstract :